Pengaruh Inflasi, Suku Bunga, Dan Nilai Tukar Rupiah Terhadap Return Saham Perusahaan Sektor Keuangan Yang Terdaftar di Bursa Efek Indonesia - Nanda Iramatul Izza, RA; Novita Indriyani; Dea Ayu Prananda; Chamariyah Chamariyah (Universitas 45 Surabaya, 2025)
Many variables can affect the company's stock returns, this study focuses on the aim to determine the effect of inflation, interest rates and rupiah exchange rates on stock returns of financial sector companies listed on the Indonesia Stock Exchange (IDX). The inflation rate, interest rate, and rupiah exchange rate are obtained from the official website of Bank Indonesia. While the value of stock returns is obtained from data from OJK (Financial Services Authority) and the financial statements of 5 banks listed on the IDX, namely BRI, Mandiri, BNI, BCA, and BTN. The entire data was taken from the last 10 years, namely from 2014 - 2024 with linear regression path analysis techniques with a 1 scheme structure pattern. Based on the results of the analysis, this study states that the effect of inflation, interest rates, and the rupiah exchange rate on financial sector stock returns on the IDX is not statistically significant. Although there is a positive relationship between inflation and stock returns, as well as a positive relationship between interest rates and stock returns, both are not strong enough to be considered significant at the 95% confidence level.